2018
DOI: 10.3389/fpls.2018.01500
|View full text |Cite
|
Sign up to set email alerts
|

PGPR Reduce Root Respiration and Oxidative Stress Enhancing Spartina maritima Root Growth and Heavy Metal Rhizoaccumulation

Abstract: The present study aims to unravel ecophysiological mechanisms underlying plant-microbe interactions under natural abiotic stress conditions, specifically heavy metal pollution. Effect of plant growth promoting rhizobacteria (PGPR) bioaugmentation on Spartina maritima in vivo root respiration and oxidative stress was investigated. This autochthonous plant is a heavy metal hyperaccumulator cordgrass growing in one of the most polluted estuaries in the world. The association with native PGPR is being studied with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(24 citation statements)
references
References 55 publications
4
20
0
Order By: Relevance
“…A significant induction of CAT removed the ROS produced during salt stress in BHU-AV3-inoculated plants. Our results are in conformity with other findings that report enhanced activities of CAT enzymes in PGPR-inoculated plants under oxidative stress (Chen et al, 2016;Mesa-Marín et al, 2018;Afridi et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…A significant induction of CAT removed the ROS produced during salt stress in BHU-AV3-inoculated plants. Our results are in conformity with other findings that report enhanced activities of CAT enzymes in PGPR-inoculated plants under oxidative stress (Chen et al, 2016;Mesa-Marín et al, 2018;Afridi et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…It has been observed that when bacteria make association with the plants, defence system of plant get activated and increased its antioxidant scavenging machinery. Inoculation-induced-alteration in antioxidant activity has also been reported by El-Esawi et al [47] and Mesa-Marín et al [48]. These strains can be efficiently deployed in extreme environments.…”
Section: Plos Onesupporting
confidence: 63%
“…Out of the various strategies that have been adopted to reverse HM-induced stress impacts in plants, the plant growth promoting rhizobacteria (PGPR) interaction is an emerging and effective sustainable way. Various recent studies in the discipline of ecological engineering and management have strongly advocated the use of PGPRs to alleviate HM-induced oxidative stress in plants, like energy crops [25], Solanum nigrum [26], Spartina maritime [27], and Lycopersicon esculentum [20,28,29]. Plant growth promoting rhizobacteria are known to induce tolerance against metal stress via modulating various intrinsic or underlying mechanisms [30].…”
Section: Introductionmentioning
confidence: 99%